The Bible as history - Keller, Werner, 1909-1980. (New York : William Morrow, 2015)
"This groundbreaking work that sheds light on the historical foundations of the bestselling book of all time--the Bible--is now updated with the latest scientific and archaeological breakthroughs in biblical investigation.No other work is as widely read throughout the world as the Bible. But did you ever wonder about its fascinating history as well as some of the scientific and historical studies that have been conducted to support the numerous accounts in the Bible? Now in this newly updated edition of The Bible As History, the latest scientific and archaeological breakthroughs in biblical investigation are revealed. This updated edition features: Remarkable evidence that confirms some of the most monumental and controversial events in the Bible, including the destruction of Sodom and Gomorra. Deciphered texts from the ancient world that offer an intriguing look back at the origin of the Ten Commandments. The extraordinary techniques used to try and prove the authenticity of the Shroud of Turin. ...and more! A breathtaking journey to the heart of Holy Scripture, The Bible As History pieces together one of the most stunning spiritual puzzles in the history of mankind." -- Publisher annotation.
A revised edition of this book was published in Great Britain in 1980 by Hodder and Stoughton.
Keywords: Bible -- History of contemporary events; Bible -- Antiquities; Bible; Antiquities; History of contemporary events